COMPARISON OF THE EFFECTS OF ALENDRONATE AND CALCITONIN ON BONE DENSITY AND BONE TURNOVER IN THE TREATMENT OF POSTMENOPAUSAL OSTEOPOROSIS - Serpil Savaş; Abdullah Cindaş; Berna Okudan; Mustafa Öztürk (Archives of Rheumatology, 2004)
The aim of this study is to compare the effects of 10 mg daily oral alendronate and intranasal calcitonin at a daily dose of 200 IU on bone density and bone turnover in the treatment of postmenopausal osteoporosis. Forty-seven patients with postmenopausal osteoporosis received alendronate therapy and thirty patients received salmon calcitonin nasal spray for 12 months. Spine and hip bone mineral density (BMD) and markers of bone turnover were measured at baseline and at 12 months. Alendronate produced greater increases in BMD than calcitonin at 12 months at the spine (p=0,05) , greater trochanter (p= 0,04) , femoral neck (p=0,05) . Alendronate produced greater decreases in serum osteocalcin levels than calcitonin (p=0,0001) and urinary deoxypridinoline (p=0,01) . We conclude that in postmenopausal women with osteoporosis, 10 mg daily alendronate produced significantly greater increases in BMD of the lumbar spine and hip and greater decreases in bone turnover than intranasal calcitonin at daily dose of 200 IU at 12 months.